Quantitative evaluation of technology used by construction enterprises - Ginevičius, Romualdas; Andruškevičius, Algirdas (Technological and Economic Development of Economy, 2004)
Methods of quantitative evaluation of construction technology focussing on two major aspects of the production program of a construction enterprise are suggested. The above methods may be applied in quantitative and qualitative analysis of technology used in construction systems of buildings and structures. The quantitative analysis aims to evaluate the uniformity of the applied methods expressed by two indices ‐ an extent of size variation of building systems and their number. The qualitative aspect reflects technological solutions of building systems contained in the production programme of an enterprise. The quantitative aspect of the applied technologies may be described in terms of size dispersion of the applied building systems. A qualitative aspect of technology concerns the extent of building systems usage and the efficiency of technological solutions. The value of the first index may be obtained from the construction program of the construction enterprise, while that of the second may be determined by expert systems. The calculations of a typical case confirm the efficiency of the suggested approach.Article in Lithuanian.Statybos įmonės technologijos kiekybinis įvertinimasFirst Published Online: 21 Oct 2010